Meat, wool and milk utilization together with comparison of F1 coming from Finnsheep rams with F1 coming from other prolific breeds - Niznikowski, R.; Tyszka, Z. J.; Janikowski, W. (Agricultural and Food Science, 1988)
The effect of crossing of Polish Corriedale (C) sheep with East Friesian, Finnsheep (F), and Polish Heath sheep was analyzed. The utility of F1 crossbreds coming from C and prolific breed rams (given above) was confirmed. The F, crosses of C ewes and F rams were characterized by the best reproductive performance, high level of milk production and the small decrease of wool quality and quantity produced by the ewes, and good carcase quality of ram lambs.